Pengaruh Dana Alokasi Khusus (DAK) dan Pendapatan Asli Daerah (PAD) Terhadap Belanja Modal Pemerintah Kota Kendari Tahun 2017-2024 - Rizal Rizal (Indo Publishing, 2026)
The aims of this study is to determine the impact of Special Allocation Funds (DAK) and Locally-Owned Revenue (PAD) on capital expenditure of the Kendari City Government from 2017 to 2025, taking into account differences in geographic and temporal context, different focuses on fiscal transfer types, the potential for more advanced methodologies, and a broader analytical scope. This study employed multiple linear regression analysis using secondary time series data from 2017 to 2025 obtained from the Central Statistics Agency (BPS). The research findings indicate that the Special Allocation Fund (DAK) significantly increases capital expenditure of the Kendari City Government, while PAD has no significant positive impact on the same capital expenditure. Suggestions for further research include expanding the research period for longer-term analysis and adding control variables such as DAU, inflation, or fiscal policy.